2011
DOI: 10.1128/jvi.05218-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Cullin5-ElonginB-ElonginC E3 Complex in Degradation of Feline Immunodeficiency Virus Vif-Mediated Feline APOBEC3 Proteins

Abstract: Various feline APOBEC3 (fA3) proteins exhibit broad antiviral activities against a wide range of viruses, such as feline immunodeficiency virus (FIV), feline foamy virus (FFV), and feline leukemia virus (FeLV), as well as those of other species. This activity can be counteracted by the FIV Vif protein, but the mechanism by which FIV Vif suppresses fA3s is unknown. In the present study, we demonstrated that FIV Vif could act via a proteasome-dependent pathway to overcome fA3s. FIV Vif interacted with feline cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 64 publications
10
52
1
Order By: Relevance
“…FIV Vif interacts with CUL5 and Elongin B/C to form an E3 complex that degrades feline APOBEC3 through a proteasome-dependent pathway (49). This is very similar to the action of HIV-1 and simian immunodeficiency virus (SIV) Vif.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…FIV Vif interacts with CUL5 and Elongin B/C to form an E3 complex that degrades feline APOBEC3 through a proteasome-dependent pathway (49). This is very similar to the action of HIV-1 and simian immunodeficiency virus (SIV) Vif.…”
mentioning
confidence: 77%
“…In addition, BIV Vif and MVV Vif inefficiently interact with CUL5 (21). Although FIV Vif could coprecipitate with CUL5, the direct interaction between FIV Vif and CUL5 is unclear (49). Thus, it needs to be determined whether FIV Vif can directly recruit CUL5 or whether the interaction is mediated by Elongin B/C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infectious molecular clone pNL4-3 and the Vif mutant pNL4-3⌬Vif construct were obtained from the National Institutes of Health AIDS Research and Reference Reagents Program (NIH-ARRRP), Division of AIDS, National Institute of Allergy and Infectious Diseases (NIAID). VR1012, A3G fused to hemagglutinin (HA) tag (A3G-HA), A3C-HA, A3F-V5, African green monkey (AGM) A3G-HA, feline A3Z3-HA ([fA3Z3-HA] where A3Z3 is the A3 protein with a Z3 domain), pHIV-1 Vif-cmyc, Vif-HA, SIVagmTan Vif-cmyc (where SIVagmTan is simian immunodeficiency virus isolated from tantalus African green monkeys), feline immunodeficiency virus (FIV) Vif-cmyc, Cullin5-HA, and ElonginC-HA have been previously described (33,34,61,67,68,71,72). A polycistronic expression vector, pST39 (57), was used to express the ElonginB/C complex in Escherichia coli.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Ai et al (2014) have shown that the conserved CBF-b interaction sequences in SIV/HIV Vif are not present in FIV Vif. Furthermore, Wang et al (2011) have reported that the FIV Vif has neither a CUL5 box nor HCCH zincbinding motif, despite a functional requirement for CUL5 in APOBEC3 degradation. Due to these extensive differences with primate lentiviral Vif proteins, it is not clear whether FIV Vif has adapted to use another cellular protein(s) or whether it is capable of functioning without a CBF-b-like co-factor.…”
mentioning
confidence: 99%